Moral Disengagement, Machiavellianism and Academic Dishonesty - Prince, Melvin; Wang, J.; Priporas, Constantinos‐Vasilios (Journal of Academic Ethics, 2025)
Keywords: Academic Dishonesty; Academic dishonesty; Big Five personality traits; Cheating; Deviance; Dishonesty; Educational Research; Machiavellianism; Machiavellianism; Social Cognitive Theory; Moral Development; Moral Disengagement; Moral Philosophy and Applied Ethics; Moral Psychology; Moral disengagement; Morality; Personality; Psychology; Social psychology; Students; dept.mrk; peer-reviewed

The Kepler follow-up observation program. I. a catalog of companions to Kepler stars from high-resolution imaging - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; van Belle, G. T.; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We present results from high-resolution, optical to near-IR imaging of host stars of Kepler Objects of Interest (KOIs), identified in the original Kepler field. Part of the data were obtained under the Kepler imaging follow-up observation program over six years (2009-2015). Almost 90% of stars that are hosts to planet candidates or confirmed planets were observed. We combine measurements of companions to KOI host stars from different bands to create a comprehensive catalog of projected separations, position angles, and magnitude differences for all detected companion stars (some of which may not be bound). Our compilation includes 2297 companions around 1903 primary stars. From high-resolution imaging, we find that ∼10% (∼30%) of the observed stars have at least one companion detected within 1″ (4″). The true fraction of systems with close (≲4″) companions is larger than the observed one due to the limited sensitivities of the imaging data. We derive correction factors for planet radii caused by the dilution of the transit depth: assuming that planets orbit the primary stars or the brightest companion stars, the average correction factors are 1.06 and 3.09, respectively. The true effect of transit dilution lies in between these two cases and varies with each system. Applying these factors to planet radii decreases the number of KOI planets with radii smaller than 2 R⊕ by ∼2%-23% and thus affects planet occurrence rates. This effect will also be important for the yield of small planets from future transit missions such as TESS. © 2017. The American Astronomical Society. All rights reserved.
161 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/078-308-144-589-565, pop00008 tex.type: [object Object]
Keywords: binaries: general; catalogs; dept.phy; peer-reviewed; planets and satellites: detection; surveys; techniques: high angular resolution; techniques: photometric

Erratum: “The Kepler Follow-up Observation Program. I. A Catalog of Companions to Kepler Stars from High-resolution Imaging” (2017, AJ, 153, 71) - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; Belle, G. T. van; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We have added references to Tables 3 and 8 (last column in each table). Below is a sample of both tables; the full tables are available in machine-readable form.
Keywords: dept.phy